Inching forward, lunging back. A duoethnographic poetic inquiry into practitioner experiences of health and ill health - Evans, Julia; Salter, Leah Karen (Murmurations: Journal of Transformative Systemic Practice, 2023)
This contribution is, in essence, a collection of poems that the two authors wrote over a period of four weeks. The temporal element is interesting. It speaks to a commitment to “go on” (Wittgenstein, 1953) at a time of illness and recovery. Duoethnography, as collaborative activity, invites new meaning by layering what could be seen as separate narratives and creating a dialogue between the evolving stories. This enables new meaning to evolve and intertwine. Undertaking an inquiry through poetry was an important decision. The intention being to provoke and promote creativity, to generate feelings of wellbeing at a time of depleted energy. Writing to and with each other was both an act of generosity and an act of self-preservation. Mutual support, maybe one way to frame it, but it was also outward looking, connecting with how we practice as therapists, how we are in the world, the causes we care about, all part of the awkward dance of living with health challenges. The poems provide their own context in a way but we have wrapped prose around the main body of the paper which is written in stanza. We feel the poetry offers a window into individual, seemingly separate experiences of ill health and a developing shared narrative of “going on”. Through the writing process, it has become clear that the poetry benefitted from the scaffolding of prose, to give the reader greater insight into the structure and sense making process. The language of inquiry speaks to what we learnt/are learning about ourselves through the process, rather than describing a research project with particular anticipated outcomes. The reflections are contained within the poems and expressed through limited words but expansive feeling. Poetic inquiry aims to humanise research with an emphasis on lived experience and researcher reflexivity. In this case the researchers and their research material could be seen as one and the same thing, an “entanglement of matter and meaning” (Barad, 2007, p. 1). But they might also be seen as separated by time and space. Since writing the pieces, new space has developed between illness and life unfolding, life that includes our practices as therapists. And new space has developed between the feelings we experienced at the time, the words we chose to convey them and how we feel now, looking back. Time and space may offer differing lenses, but maybe not. The paper as a whole is an example of writing from within lived experience, written in poetic form. The form supported the authors to write their way through illness and into new territory of living with and beyond life impacting health conditions.